Valuing the avoidance of IQ losses in children A large scale multi-country stated preference approach - Mourato, Susana (OECD Publishing, 2023)
Exposure to chemicals has been shown to reduce IQ in children. In turn, a person's IQ is likely to affect their educational achievements, which may then affect lifetime earnings, more generally, a person's quality of life. At the same time, authorities face challenges in regulating chemical substances through actions such as bans and prohibitions, because of the difficulty in explicitly considering the economic benefits and costs of such regulations. Moreover, economic studies that show the value of reducing IQ loss caused by chemical exposure are not yet available. This paper is part of the series of large scale willingness to pay (WTP) studies resulting from the Surveys to elicit Willingness to pay to Avoid Chemicals related negative Health Effects (SWACHE) project that intends to improve the basis for doing cost benefit analyses of chemicals management options and environmental policies in general. The present paper details a stated preference survey estimating WTP to avoid IQ loss, filling an important gap in the valuation literature and addressing a need for applied benefits analysis for chemicals regulation. The SWACHE IQ loss survey was fielded in 11 countries: Australia, Canada, Denmark, Korea, Netherlands, Poland, Portugal, South Africa, Sweden, the United Kingdom and the United States
Keywords: Environment; Social Issues/Migration/Health